Alterações de memória e flexibilidade cognitiva em modelo animal de sintomas não-motores de Doença de Parkinson induzido por 6-hidroxidopamina (6-ohda) - Clara de Paula Gomes (2024)
Parkinson's Disease (PD) is classically characterized by the loss of dopaminergic neurons in the Substantia Nigra (SN) and recognized by its motor symptoms. However, a significant body of evidence indicates that PD affects several other neurotransmitter systems, causing non-motor symptoms. Cognitive alterations such as Parkinson's disease dementia and decreased executive functions are part of a group of non-motor symptoms that can be developed throughout the disease. The treatment and knowledge of the evolution of these non-motor symptoms can improve the quality of life of these patients. In this study, we evaluated whether the partial lesion of the nigrostriatal pathway induced by the neurotoxin 6-hydroxydopamine (6-OHDA) in rats would be sufficient to reproduce some of the non-motor symptoms of PD. In particular, we investigated possible alterations of memory and executive functions of the animal model in question. Adult male Wistar rats were anesthetized and underwent stereotaxic surgery for bilateral infusion of 10μg of 6-OHDA diluted in 3μL of solution containing ascorbic acid in the striatum. Animals in the control group received only the vehicle of the drug. First, motor tests were performed to confirm the absence of severe motor symptoms that would compromise the other tasks. In addition, we analyzed possible anxiety-like behaviors in the open field test. With the confirmation that the animals displayed neither anxiety-like alterations nor motor symptoms, we performed tests to examine memory, learning, and executive functions. When we evaluated the animals in the Barnes Maze, we observed a significant impairment in spatial memory in the 6-OHDA group, showing less time in the target quadrant in the retrieval test. In the reverse learning test, used to analyze cognitive flexibility, the 6-OHDA animals needed more trials to learn the new location, without increasing the number of visits to the previous target quadrant. In conclusion, the partial lesion of the nigrostriatal pathway induced by 6-OHDA was sufficient to reproduce some non-motor symptoms observed in the clinic, such as memory impairment and behavioral flexibility. We hope that our findings will support future investigations into the mechanisms underlying the mnemonic and executive function alterations observed in PD.